Proportion of Allergic Rhinitis in Asthma Patient and Their Correlation with Asthma Control - Fersia Iranita Liza; Wiwien Heru Wiyono; Deasi Anggraini; Erlang Samoedro; Triya Damayanti (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2021)
Background: Upper and lower airway diseases have strong interaction, particularly between asthma and AR. SPT and nasal endoscopy are not always used as tools for diagnosing AR. This study aimed to determine proportion of AR in asthma patients and the correlation with asthma control. Methods: This was a cross sectional study in 185 adult patients with asthma. Nasal endoscopy was used to objectively obtain data on the anatomical condition of nose and paranasal sinus orifices. Allergic rhinitis severity was classified according to the ARIA system. The ACT questionnaire was used to assess asthma control and allergic reactions were measured using SPT with 12 allergens. Results: A total of 54 asthma patients (29.2%) had AR. The most common allergens were house dust mite (38.8%), house dust (37.3%), and human skin flakes (32.8%). The results of nasal endoscopy showed that there were septum deviation (56.6%), pale concha (50.9%), edematous concha (22.6%), hypertrophic concha (18.9%), sinusitis and polyp (16.9%, respectively). The results of ACT questionnaire showed a score of ≤19 (uncontrolled asthma) found in 45.9% asthmatic patients, partially control in 47% patients and controlled asthma in 7% patients. Based on AR severity, it was obtained those with mild intermittent (46.3%), mild persistent (46,3%) and moderate-severe persistent AR (7.4%). There was a significant correlation between AR and asthma control (P=0,045). Conclusions: AR is a common comorbid in asthmatic patients. Precipitating allergens could be detected by SPT in asthmatic patients with AR. Avoiding exposure to precipitating allergens could prevent exacerbation in asthmatic patients with AR.